Brain Mapping – Neuromuscular correlations in long-term Postsurgical rehabilitation of Adult Brachial Plexus Palsies - Dan Trofin; Cristina Grosu; Daniel Andrei Iordan; Daniela-Marilena Trofin; Ilie Onu; Teodor Stamate; Daniela-Viorelia Matei (Balneo and PRM Research Journal, 2024)
Background: Correlations of Transcranial magnetic stimulation (TMS) mapping of the cortical area and electromyography (EMG) + dynamometric testing may demonstrate active neuro-plas-ticity events that are reliant on rehabilitation therapy (RT) compliance in adult postsurgical brachial plexus (BP) injuries. Material and Methods: On the right (dominant) arm of two patients with chronic operated BP lesions, we evaluated the progress of functional recovery. The trau-matic event was dated more than 10 years ago for both patients. The first patient (male, 50 years old) and the second one (female, 58 years old) had a history of several microsurgical neu-rotiza-tion and muscle transfer procedures, with less amelioration of the motor deficit, especial-ly re-lated to elbow flexion (MRC 1/5 and 2/5, respectively). We followed up their evolution by EMG parameters, dynamometry, MRC scaling, and TMS. The motor region of the limb was mapped using TMS to assess the amplitudes of the motor evoked potentials (MEP), on a 4-axis protocol. The patients were assessed twice, with the second examination performed after RT had just fin-ished. TMS findings were compared with EMG and dynamometric results. Results: High-er MEP amplitudes were associated with improved MEP latency during stimulation of the left cerebral hemisphere's cortical area, as well as at the cervical level. EMG findings, both nerve conduction and needle EMG studies showed nonsignificant improvements, as well as muscle strength (as measured by the hydraulic dynamometer). The best results for the first patient showed an in-crease in MEP’s amplitude increase from 1.08 mV to 1.49 mV (in the hotspot), which correlated with measurable latencies, as compared to the first TMS (when no response was obtained at cer-vical stimulation). The second patient also had improvements in latencies: from 37.1 msec. to 36.3 msec. (cervical stimulation with recording at bicipital level) and from 39.2 msec. to 37.9 (cervical stimulation recording at the first interosseous), with a hotspot increase from 1.35 mV to 1.98 mV. The results demonstrate cortical region reactivity in regard to thera-peutic techniques. Central modifications do not correlate with visible EMG and dynamometric improvements. Pa-tients with traumatic BP palsy may receive several microsurgical reconstruc-tive procedures, nevertheless, the rehabilitation of the upper limb’s functionality may some-times still be limited. This increases the risk of discontinuity of the neuromotor RT. We aim to prove that in spite of little correlations with clinical and EMG findings, mapping the cortical area using TMS provides proof of ongoing neuroplasticity phenomena, dependent on adherence to RT. Conclusion: The evidence of continued brain activity supports the requirement for long-term adherence to treatment guidelines and long-term study protocols.